2022
DOI: 10.1007/s12672-022-00501-5
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of long noncoding RNA linc02544 and its association with overall survival rate and the influence on cell proliferation and migration in lung squamous cell carcinoma

Abstract: Background Long noncoding RNAs (lncRNAs) exert crucial biological functions by regulating miRNAs, which are implicated in cancer progression and tumorigenesis. A previous study has indicated that lncRNA linc02544 expression is upregulated in lung adenocarcinoma, whereas, the role of linc02544 in LUSC is elusive. Methods The differential linc02544 expression in LUSC tissues and adjacent non-tumor tissues were evaluated with RT-qPCR. Kaplan-Meier cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Previous data about the influence of these lncRNAs in invasion or metastasis and unfavorable prognosis can be found in other cancers and reinforce our findings. LINC02544 is overexpressed in lung squamous cell carcinoma patients with lymph node metastasis, and it promotes proliferation, migration, and invasion in vitro by sponging miR-138-5p—a potential target of E2F3 [ 91 ]; increased expression of LINC02544 has also been related to in vitro invasion and unfavorable prognosis in breast cancer [ 92 ]. LINC01235 is upregulated in gastric cancer patients versus healthy individuals and metastatic versus non-metastatic gastric cancer patients, promoting migration, invasion, and EMT, as well as negatively affecting prognosis [ 93 , 94 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous data about the influence of these lncRNAs in invasion or metastasis and unfavorable prognosis can be found in other cancers and reinforce our findings. LINC02544 is overexpressed in lung squamous cell carcinoma patients with lymph node metastasis, and it promotes proliferation, migration, and invasion in vitro by sponging miR-138-5p—a potential target of E2F3 [ 91 ]; increased expression of LINC02544 has also been related to in vitro invasion and unfavorable prognosis in breast cancer [ 92 ]. LINC01235 is upregulated in gastric cancer patients versus healthy individuals and metastatic versus non-metastatic gastric cancer patients, promoting migration, invasion, and EMT, as well as negatively affecting prognosis [ 93 , 94 ].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple projects have shown that lncRNAs are associated with the prognosis and the growth of cancer cells [12][13][14][15] . Glioma tissues and cells showed signi cant downregulation of p53 expression and a signi cant increase in lncRNA PVT1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…NcRNAs represent a subclass of RNAs that are transcribed but not translated with different lengths, structures, and functions. Interestingly, their interactions with other cellular RNAs and/ or proteins contribute to the creation of an intricate network capable of shaping cellular phenotypes through the regulation of both cellular transcription and translation, so that ncRNAs act as epigenetic regulators [21] which impact on cell proliferation, differentiation, cell death and metabolism, especially in cancer [22][23][24][25]. Long Non-Coding RNA (lncRNAs), a group of ncRNA longer than 200 nucleotides, are already known to play important roles in skin homeostasis, such as for example the Anti-Differentiation ncRNA (ANCR) and the Terminal-Differentiation Induced ncRNA (TINCR), which can regulate epidermal proliferation and differentiation, respectively [26,27].…”
Section: Introductionmentioning
confidence: 99%